Intensive Care Research - Jiang, Yong.; Sun, Tongwen; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Aims and scope Intensive Care Research provides a platform for the communication and exchange of latest news, ideas and findings in all disciplines of critical and intensive care medicine worldwide. Intensive Care Research encourages research covering the current key research interests in discussing the process of intensive care pathophysiology, management, and new technologies. Topics covered include, but are not limited to: mechanical ventilation, multidrug resistant bacteria (MDR), encephalopathy, cardiovascular Emergency, artificial intelligence and big data in intensive care, sepsis, acute respiratory distress syndrome (ARDS), epidemiology, multiple organ dysfunction syndrome (MODS), etc. The journal publishes a range of article types including original research articles, reviews, expert guidelines, case reports, perspectives, commentaries and protocols. .
Keywords: Medicine; Clinical Medicine